The effect of Used Cooking Oil (UCO) pre-treatment using bagasse on Free Fatty Acid (FFA) content - Haryani, Nina; Utami, Andiga Asih Ambarwati; Imanda, Elfrida Rasyidah Desvi (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Used Cooking Oil (UCO) refers to cooking oil that has been previously used. UCO can be reused through impurity removal and reduction of the FFA high content. The reduction of FFA content in UCO can be achieved using the adsorption method, employing adsorbents derived from various materials such as agricultural waste and zeolite. Examples of agricultural waste suitable for this purpose include rice husks, straw, and bagasse, the latter of which can serve as a natural adsorbent. This study aimed to investigate the impact of UCO pre-treatment on FFA content. The research comprised three stages: preparation, adsorption, and analysis. Initially, the FFA content in UCO was 5.50 %. The pre-treatment of UCO involved using bagasse with varying stirring speeds (0, 150, 200 rpm) and adsorption temperatures (70, 85, 100 oC). Optimal pre-treatment conditions were identified, with the most significant reduction in FFA to 1.49 % observed at 200 rpm and 100 oC. The utilization of bagasse as a natural adsorbent effectively reduces the high FFA content in UCO as part of its pre-treatment process.